Immunogenicity and safety of concomitant administration of meningococcal serogroup B (4CMenB) and serogroup C (MenC-CRM) vaccines in infants: A phase 3b, randomized controlled trial. Issue 16 (11th April 2017) - P. Safadi, Marco Aurelio; Martinon-Torres, Federico; Weckx, Lily Yin; Moreira, Edson Duarte; da Fonseca Lima, Eduardo Jorge; Mensi, Ilhem; Calabresi, Marco; Toneatto, Daniela
Abstract: Background: After implementation of routine infant MenC vaccination, MenB remains a serious cause of meningococcal disease, yet to be targeted by vaccination programs in several countries. This study (NCT01339923 ) investigated the immunogenicity and safety of MenC CRM-conjugated vaccine (MenC-CRM) concomitantly administered with MenB vaccine (4CMenB). Methods: Infants (N = 251) were randomised 1:1 to receive 4CMenB and MenC-CRM (Group 1) or MenC-CRM alone (Group 2) at 3 and 5 months (M3, M5) and a booster at 12 months of age (M12), and pneumococcal vaccine at M3, M5, M7, M12. Antibody responses to meningococcal vaccines were measured at M3, M6, M12, and M13. Non-inferiority of MenC-CRM response in Group 1 vs Group 2 was demonstrated at M6 and M13, if the lower limit of the 95% confidence interval (LL95%CI) of the difference in percentage of infants with hSBA titres ≥1:8 was >−10%. Sufficiency of MenB response was achieved if LL95%CI of the percentage of infants with hSBA titres ≥1:4 against fHbp, NadA and PorA strains was ≥70% at M6 or ≥75% at M13. Adverse events (AEs) were collected for 7 days post-vaccination, and serious AEs (SAEs) and medically attended AEs throughout the study. Results: Non-inferiority of MenC response in Group 1 vs Group 2 (LL95%CI −6.4% [M6]; −5.2% [M13]) and sufficiency of MenB response in Group 1 (LL95%CI 92%, 90%, 89% [M6]; 97%, 92%, 93% [M13] against fHbp, NadA, PorA, respectively) were demonstrated. Higher rates of mild to moderate solicited AEs were reported in Group 1. Unsolicited AEs and SAEs incidences were similar across groups. Conclusions: Concomitant administration of MenC-CRM and 4CMenB in infants was immunogenic, resulting in non-inferior responses against MenC compared to MenC-CRM alone and demonstration of sufficient immune response to MenB, after primary and booster vaccination. Reactogenicity was higher for concomitant vaccines administration, but no safety concerns were identified. Author Video: Author Video Watch what authors say about their articles